Membaca Ruang Publik dan Jurnalisme dalam Perspektif Jürgen Habermas - Hasan, Moh. Fathul (Perspektif, 2019)
The long history of journalism is in line with the progress of the concept of public sphere. This artidle tries to analyse the public journalism using Jürgen Habermas’ idea on the ontology of public sphere, the history of press, and the relation between public sphere and press. This research was carried out using the bibliographical study on journalism and public sphere. The findings show that the concept of public in the public sphere is quite different from the one in history. The writer finally found out the concept of public sphere which is in accordance with our contemporary concept. Public sphere in Habermas’ opinion has two forms: public sphere in politics and in literature. With these two concepts, the writer will explain the connection between public sphere and press in Habermas’ opinion in such a way that finally came out the concept of public journalism.